Analysis of Freedom of Expression: A Case Study on Religious Court Decision Number 726/PID SUS/2023/PN PLG - Ardi Eka Kurniawan; M. Junaidi; Yoesoef Moestofa; Natangsa Surbakti; Bambang Sukoco (Proceeding International Conference Restructuring and Transforming Law, 2024)
This study aims to understand and analyze the judicial consideration that affects freedom and the review of freedom of expression on social media according to positive law. This juridical-normative study is examined using descriptive analysis method and legislative approach. The data examined are obtained from secondary data sources consisting of primary and secondary legal materials. The results of the research show that the legal case in Religious Court Decision Number 726/PID SUS/2023/PN PLG related to religious blasphemy on social media, when associated with freedom of opinion and expression, may disrupt the judge's decision-making and imposition of sanctions because the judge's decision can trigger reactions that may lead to conflicts among society, causing negative perceptions regarding the law's clarity in handling the issue and significant impacts such as the emergence of similar cases and their association with freedom of expression when someone violates legal regulations. The implementation of law enforcement regarding freedom of expression concerning religious blasphemy on social media is not uniform and comprehensive. Based on the findings of the study, religious blasphemy on social media is still not optimally addressed by the existing laws. The aim of law enforcement is to protect all religions and ensure the protection of individual rights in expressing opinions. Legal actions are expected to comply with applicable laws and not hinder the judicial decision-making process in handling cases related to religious blasphemy and freedom of expression.